2006
DOI: 10.1007/s00066-006-1498-8
|View full text |Cite
|
Sign up to set email alerts
|

Intensified External-Beam Radiation Therapy Improves the Outcome of Stage 4 Neuroblastoma in Children > 1 Year with Residual Local Disease

Abstract: EBRT appeared effective in high-intensive treatment of stage 4 neuroblastoma. It seems to compensate the disadvantage of incomplete response to induction chemotherapy. These retrospective results need confirmation by a prospective randomized trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(46 citation statements)
references
References 29 publications
2
43
0
1
Order By: Relevance
“…Recently IORT has been described in a cohort of pediatric patients with varying benign conditions and malignancy [5]. EBRT also has been described that it was effective in advanced neuroblastoma [19][20][21]. The importance of intensive local treatment for advanced neuroblastoma was emphasized in other studies [22][23][24][25][26].…”
Section: Discussionmentioning
confidence: 97%
“…Recently IORT has been described in a cohort of pediatric patients with varying benign conditions and malignancy [5]. EBRT also has been described that it was effective in advanced neuroblastoma [19][20][21]. The importance of intensive local treatment for advanced neuroblastoma was emphasized in other studies [22][23][24][25][26].…”
Section: Discussionmentioning
confidence: 97%
“…Locoregional control rates in different studies have ranged from 25% to 61% when no RT was used compared to 84% to 100% with systematic use of primary site RT (21-21.6 Gy to the primary site). Some studies have also suggested that a higher dose of RT may be needed for patients who do not achieve a GTR (8)(9)(10). A previous German study reported a 3-year event-free survival of 85% in patients with subtotal resection who received a median dose of 36 Gy (30.6-40 Gy).…”
Section: Discussionmentioning
confidence: 99%
“…1,33,34 A further development is the use of high doses of MIBG either alone or in addition to TBI and local radiotherapy, which may increase the chance of eradicating small tumour deposits. 35 8. The use of MIBG in place of TBI has been proposed in pilot studies 36,37 and was used in trial settings.…”
Section: Discussion and Future Perspectivesmentioning
confidence: 99%